Toward an Ethical Model of Effective Crisis Communication. (March 2015) - Kim, Young
Abstract The goal of this study was to develop and demonstrate a new ethical model for crisis communication. This article examined the crisis communication practices as well as literature and found essential elements—what, how, and when—for ethical and effective crisis communication. Based on these three variables, a new three‐part model, the TTR Test, was proposed, utilizing three principles: Transparency (what), Two‐way symmetrical communication (how), and Right time (when). To investigate how the test can be applied to the real world, this article examined BP's crisis communication during the 2010 Gulf of Mexico oil spill.